Effects of lift-assist device on trunk and shoulder kinematics - Ashish D. Nimbarte; Suman Kanti Chowdhury; Christopher W. Moore (Occupational Health and Safety Society of Nepal, 2017)
Background: Repetitive handling of heavy concrete blocks has been associated with the risk of low back and shoulder injuries among the masons. Several interventions have been proposed to reduce the risk of musculoskeletal disorders among the masons. A new intervention, a lift-assist handle, was tested in this study. Objective: The effectiveness of the lift-assist handle in masonry work was assessed using the shoulder and low back  kinematics  during  block  lifting/lowering  tasks  performed  at  two  heights. Methods: In a laboratory setting, seven male subjects performed with- and without-lift handle assisted block lifting tasks at two different heights.  Optical motion capture system and biomechanical modeling software were used to record and model each dynamic trial. Effect of lifting height and use of a lift-assist handle on range of motion of the shoulder and trunk were tested. Results: The use of lift-assist handle significantly reduced trunk motion and increased shoulder motion. Lifting height had a significant effect on shoulder kinematics only. When height was increased from 17to 29 inches, the ranges of motion of  shoulder abduction-adduction and internal rotation significantly increased. Additionally, block lifting/lowering task duration decreased by 26% when the lift-assist handle was used. Conclusions: While  potential benefits to lower back health were found with the lift-assist handle, increased shoulder motion may increase the risk of shoulder injuries. The findings of this study emphasize the need for an in-depth analysis of assistive devices prior to implementation to ensure that there are no unintended consequences of their use that could negate their benefit.